Gene therapy in peripheral artery disease. (March 2015) - Sanada, Fumihiro; Taniyama, Yoshiaki; Kanbara, Yasuhiro; Otsu, Rei; Ikeda-Iwabu, Yuka; Carracedo, Miguel; Rakugi, Hiromi; Morishita, Ryuichi
<x xml:space="preserve">Abstract</x> Introduction: Despite the remarkable progress of medicine and endovascular procedures for revascularization, patients with critical limb ischemia (CLI) remain at high risk for amputation and often have a low quality of life due to pain and ulcers in the ischemic leg. Thus, a novel strategy for generating new blood vessels in CLI patients without treatment options is vital. Pre-clinical studies and Phase I clinical trials using VEGF and fibroblast growth factor (FGF) demonstrated promising results; however, more rigorous Phase II and III clinical trials failed to demonstrate benefits for CLI patients. Recently, two multicenter, double-blind, placebo-controlled clinical trials in Japan (Phase III) and the USA (Phase II) showed the benefits of hepatocyte growth factor (HGF) gene therapy for CLI patients. Although the number of patients included in these trials was relatively small, these results imply a distinct beneficial function for HGF over other angiogenic growth factors in a clinical setting. Areas covered: In this review, data from Phase I–III clinical trials of gene therapy for patients with peripheral artery disease (PAD) are examined. In addition, the potential mechanisms behind the success or failure of clinical trials are discussed. Expert opinion: Compared with VEGF and FGF, HGF has a unique molecular effect on inflammation, fibrosis and cell senescence under pathological conditions. These features may explain the clinical benefits of HGF in PAD patients.